Dielectric properties of cereal stubble infected with Bipolaris sorokiniana, Fusarium pseudograminearum and Pyrenophora teres in the microwave frequency range. Issue 4 (18th November 2022) - Petronaitis, Toni; Brodie, Graham; Simpfendorfer, Steven; Flavel, Richard J.; Warwick, Nigel W. M.
Abstract: Cereal production in Australia is severely impacted by stubble-borne pathogens which can survive multiple seasons within cereal residues (stubble). Microwave radiation may be able to reduce or eliminate the pathogens, but the energy requirements first need defining. Hence, the dielectric properties of wheat and barley stubble with different pathogen loads were investigated at 10%, 15%, 30% and 100% moisture content using an open-ended coaxial probe in a spectral band covering 915, 2450, and 5800 MHz. A significant increase in dielectric constant and loss factor was observed with increasing stubble moisture. The dielectric constant and loss factor were lower in the crown (basal) section of stubble compared with the stem (20 cm from base), due to differences in density. When stubble moisture was 100%, the loss factor of barley was higher than wheat. Infection of stubble by different pathogens did not affect the dielectric properties. Microwave heating could therefore be an effective method to heat cereal stubble to eradicate a range of cereal pathogens, especially at lower frequencies and high moisture content, at which the loss factor is high. This research serves as a starting point to define requirements for further development of effective microwave radiation treatments under field conditions.